Diagnostic accuracy of RIPASA scoring system against Alvarado score in acute appendicitis - Karki, Om Bahadur; Timilsina, Bishwodeep (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Acute appendicitis is a common surgical emergency. A number of scoring systems have been used to assist in equivocal cases in aiding in early diagnosis and decrease negative appendicectomy rates. Alvarado score is the most popular scoring system and recently The Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) has been designed for the diagnosis of acute appendicitis in the Asian population. The aim of this study was to evaluate the RIPASA score and compare its performance in predicting risk of appendicitis with the Alvarado score. METHODS We compared Alvarado and RIPASA scoring system by applying them to 204 patients who presented with right iliac fossa pain in Manipal Teaching Hospital, Pokhara, Nepal between January 2022 and December 2024. Ethical clearance was taken. Statistical analysis was done using SPSS 21 and p value <0.05 was considered significant. RESULTS The study included 204 patients 114 (55.9%) males and 90 (44.1%) females. The mean age of patients was 26.44 ±15.52 years. RIPASA showed better sensitivity of 97.39%as compared to 89.58% of Alvarado score. The positive and negative predictive values of Alvarado score were 96.12% and 12.24%, as compared to 96.35% and 44.16% for RIPASSA score. Furthermore, the area under receiver operating curve of the RIPASA was better (0.690) than that of Alvarado score (0.638). CONCLUSION RIPASA score is more accurate with high specificity and sensitivity in diagnosing acute appendicitis than Alvarado scoring system in Nepalese population and in preventing negative appendectomies.